Anatomical variant of physeal blood supply to the fibula. Issue 6 (7th June 2021) - Mantelakis, Angelos; Mughal, Maleeha; Man, Julian; Roblin, Paul
Abstract : Vascularised epiphysial fibula bone transfers in the paediatric population provides a solution to growth suppression in extremity reconstruction. We report a case of an anatomical variant to the epiphysial blood supply that has never been reported in literature. A 6-year-old girl underwent a free vascularised fibula flap for reconstruction of her right humerous following osteosarcoma resection. While identifying and dissecting the recurrent epiphysial branch, a large branch from the peroneal artery was identified which directly entered the head of the fibula. No dominant supply from the anterior tibial (AT) vessels to the head of the fibula was seen. This led to the need for a bipedicled flap with diaphyseal supply from the AT vessels and the epiphysial transfer based on the peroneal artery. The patient made an uneventful recovery from the procedure. The same technique may be used by surgeons that may encounter this unique variant in clinical practice.